Persistence of Antibody After a Vi-Tetanus Toxoid Conjugate Vaccine and Effect of Boosting With a Plain Polysaccharide Vaccine on Vi Antibody and Antigen-Specific B Cells - Bentley, Thomas; Jones, Elizabeth; Jin, Celina; Moore, Maria; Gardner, Jonathon; Hill, Jennifer; Pollard, Andrew J. (Frontiers in Tropical Diseases, 2021)
Background Salmonella enterica serovar Typhi is estimated to cause 9 to 13 million cases of typhoid fever annually. Typhoid conjugate vaccines represent a promising prophylactic measure to prevent disease, but there are few data assessing persistence of immunity. The effect of a Vi polysaccharide booster vaccine in individuals previously vaccinated with the Vi-tetanus toxoid typhoid conjugate vaccine has not been assessed previously. Methods Thirty five healthy adult volunteers received a single dose of the Vi conjugate vaccine (Vi-TT) and 37 received a single dose of Vi polysaccharide vaccine (Vi-PS) prior to oral challenge with live S. Typhi bacteria as part of a randomised controlled, phase 2b study. In addition to data previously published showing persistence of Vi IgG and IgA antibodies for 7 months after Vi vaccination, titres were measured at intervals until 13 months post-vaccination. Ten participants who received Vi-TT (both challenged and unchallenged) were re-vaccinated with Vi-PS at an interval of 19-23 months post-prime. Anti-Vi IgG and IgA titres, and Vi-specific antibody secreting cells and memory B cells were measured at seven days and one month post-boost. Findings Vi IgG and IgA antibody titres remained significantly elevated above baseline levels 13 months after priming with Vi-TT, with a 4-fold rise retained in 90% and 88% of recipients (Vi IgG and IgA, respectively). Anti-Vi IgG and IgA antibody titres were found to persist at higher levels in participants who received a single dose of Vi-TT than in those who received Vi-PS. No significant boost in Vi-antibody titre was observed in response to oral challenge with S. Typhi bacteria, one month after vaccination. Following a Vi-PS booster vaccination in those previously vaccinated with Vi-TT, anti-Vi IgG and IgA titres were significantly elevated, with similar titres observed at one month post-boost compared with one month after primary vaccination. The frequency of Vi-specific IgA antibody secreting cells increased significantly 7 days post-boost compared with pre-boost. No memory B cell response was observed following Vi-PS booster vaccination. Interpretation Strong persistence of anti-Vi IgG and IgA following Vi-TT vaccination suggests that the conjugate vaccine may offer durable protection, supporting its use in endemic settings.